TINJAUAN YURIDIS TERHADAP PERATURAN MENGENAI PENCABUTAN PERMOHONAN KASASI DALAM PENYELESAIAN PERKARA PERDATA - Jesica Dewi (Universitas 17 Agustus 1945 Samarinda, 2014)
ABSTRACT If the parties are not satisfied a civil litigant against a High Court ruling and do not want to accept the decision, he may apply to the Supreme Court of Cassation within the meaning of Act No. 3 of 2009 on on the Second Amendment Act No. 14 of 1985 on the Supreme Court. The appeal is entitled to the litigants themselves, because it was he who acted as a material, which is directly involved in the conflict are sued (to be a party to the conflict). Appeal does is aimed to assess whether the lower levels of the judge's decision, whether the decision dibuattelah accordance with the provisions of law and procedural law, so that the litigants get justice fairest. Cassation judge's ruling also allows the improvement caused by the judge 's own fault or human error, because the judges are also human nature that can make mistakes. Another issue with respect to these issues is concerned repeal cassation appeal itself, where the legislation does not provide further details on the matter. According to the Supreme Court 's jurisprudence, that revocation appeal is allowed as long as the decision was not handed down by the Supreme Court, if there is an appeal of the revocation of both the litigants, the proceedings in the Supreme Court not be done or stopped, but if only one party only cassation petition is revoked, while others who also did not revoke the petition filed cassation appeal, cassation proceedings levels remain to be done. Revocation appeal, should be strictly regulated and clearly in the National Civil Procedure, so that revocation appeal made by the litigants do not harm any of the parties who were also litigants in the case, so that the revocation appeal is conducted aiming to resolve cases exists and is not intended to harm the litigants.